Peripheralization
320 p.
Keywords: Peripheries emerge as a result of shifts in economic and political decision-making at various scales. Therefore peripheral spaces are not a “natural” phenomenon but an outcome of the intrinsic logic of uneven geographical development in capitalist societies. Discussing examples from Germany, Eastern Europe, Turkey, Iraqi Kurdistan, Pakistan, India and Brazil, the volume describes the social production of peripheries from different theoretical and methodological perspectives. In so doing, it argues in favour of a re-politicization of the recent debate on peripheralization.